Appropriate clinical use of human leukocyte antigen typing for coeliac disease: an Australasian perspective. Issue 4 (April 2015) - Tye‐Din, J. A.; Cameron, D. J. S.; Daveson, A. J.; Day, A. S.; Dellsperger, P.; Hogan, C.; Newnham, E. D.; Shepherd, S. J.; Steele, R. H.; Wienholt, L.; Varney, M. D.
Abstract The past decade has seen human leukocyte antigen (HLA) typing emerge as a remarkably popular test for the diagnostic work‐up of coeliac disease with high patient acceptance. Although limited in its positive predictive value for coeliac disease, the strong disease association with specific HLA genes imparts exceptional negative predictive value to HLA typing, enabling a negative result to exclude coeliac disease confidently. In response to mounting evidence that the clinical use and interpretation of HLA typing often deviates from best practice, this article outlines an evidence‐based approach to guide clinically appropriate use of HLA typing, and establishes a reporting template for pathology providers to improve communication of results.